Nursing Faculty Job Satisfaction and Intent to Stay in Academia - Jones‐Darnell, Tracy (My University, 2017)
The retention of nursing faculty is a growing concern in the United States and a major challenge for the nursing profession. The purpose of this study was to examine the causal effects among the variables mentoring, job stress, incivility, organizational commitment, and occupational commitment on nursing faculty job satisfaction and intent to stay in academia. A structural equation model was generated and tested to examine the relationships among variables and to identify the direct effects, indirect effects, and total effects on job satisfaction and intent to stay in academia. The sample consisted of 118 associate degree nursing faculty in the state of Georgia who were primarily female, Caucasian, master’s prepared, and employed full-time in academia. Nursing faculty responded to the 87-item Nursing Faculty Job Satisfaction Questionnaire which was created from six previously validated instruments. The Pearson’s correlations among variables were positive and moderately correlated except for the variables of job stress and incivility which were negative and moderately correlated with the other variables. Occupational commitment and organizational commitment had the strongest, positive correlations with job satisfaction and intent to stay. Incivility had the smallest correlation with intent to stay, whereas mentoring had the smallest correlation with job satisfaction. In the final path model, the variables organizational commitment, job stress and occupational commitment were the strongest predictors of job satisfaction. The variables occupational commitment, organizational commitment, and job satisfaction were the strongest predictors of nursing faculty intent to stay in academia.
Chapter I: INTRODUCTION 1 | Statement of the Problem 6 | Purpose of the Study 7 | Research Questions 8 | Research Methodology 9 | Significance of the Study 11 | Theoretical Framework 12 | Limitations of the Study 15 | Definition of Terms 15 | Organization of the Study 17 | Chapter II: LITERATURE REVIEW 18 | Future of Nursing 19 | Healthcare Reform 21 | Nursing Shortage 23 | Nursing Faculty Shortage 24 | Nursing Education 27 | Program Type 31 | Nursing Faculty Work life 33 | Individual Characteristics 35 | Job Stress 37 | Incivility 38 | Moral Distress 41 | Role Conflict 44 | Leadership 46 | Faculty Salaries 48 | Workload 49 | Mentoring 51 | Organizational Commitment 53 | Occupational Commitment 56 | Job Satisfaction 58 | Intent to Leave 66 | Intent to Stay 70 | Chapter III: METHODOLOGY 74 | Research Design 74 | Participants 74 | Instrumentation 75 | Faculty Stress Index 77 | Nursing Faculty Satisfaction Questionnaire 77 | Incivility in Nursing Education Survey 78 | Organizational Commitment Questionnaire 79 | Occupational Commitment Instrument 80 | Mentoring 81 | Intent to Stay 81 | Demographic Characteristics 82 | Instrument Development 82 | Data Collection 84 | Data Analysis 85 | Statistical Considerations and Assumptions 88 | Summary 90 | Chapter IV: RESULTS 91 | Demographic Characteristics of ADN faculty 92 | Item-Level Descriptive Statistics 94 | Scale Descriptive Statistics 102 | SEM Model Assumptions and Analysis 105 | Descriptive Statistics and Correlations after Data Transformation 108 | Summary 126 | Chapter V: SUMMARY AND DISCUSSION 128 | Related Literature 128 | Methodology 136 | Summary of Findings 138 | Discussion of Findings 139 | Limitations of the Study 147 | Implications for Future Research 148 | Conclusion 150 | REFERENCES 152 | APPENDIX A: Institutional Review Board Approval from Valdosta State University.173 | APPENDIX B: Letter to Dean or Director 175 | APPENDIX C: Letter to Participant 177 | APPENDIX D: Nursing Faculty Job Satisfaction and Intent to Stay Questionnaire …..179 | APPENDIX E: Permission to use Faculty Stress Index 186 | APPENDIX F: Permission to use Dreher and Ash’s Mentoring Scale 188 | APPENDIX G: Permission to use the Occupational Commitment Instrument 190
Keywords: Nursing; Faculty; Job satisfaction; Employee retention; Nurses; Georgia